1998
DOI: 10.1080/00103629809370140
|View full text |Cite
|
Sign up to set email alerts
|

Influence of simulated erosion on soil properties and maize yield in Northwestern India

Abstract: Laboratory and field experiments were conducted at the Regional Research Station of Kandi Area, Ballowal Saunkhri, Punjab, India, to determine the immediate influence of artificial topsoil removal (simulated erosion) on selected soil properties, maize (Zea mays) growth and yield, and restoration of crop productivity with nitrogen (N) fertilization. For the laboratory experiment, soil samples (0-15 cm) were obtained after removing 0, 6, 12, and 18 cm of a sandy loam topsoil from a cereal grain cropped field. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The mean annual rainfall in the region is 1040 ± 150 mm, of which more than 80 per cent is received during the summer monsoon months (July to September). The probability of expecting at least one dry spell greater than 6 days during individual months varies between 55 and 99 per cent (Sur et al ., ). The mean maximum temperatures vary from 18·6°C in January to 39·1°C in May, and mean minimum temperatures vary from 5·2°C in December to 24·7°C in June.…”
Section: Methodsmentioning
confidence: 97%
“…The mean annual rainfall in the region is 1040 ± 150 mm, of which more than 80 per cent is received during the summer monsoon months (July to September). The probability of expecting at least one dry spell greater than 6 days during individual months varies between 55 and 99 per cent (Sur et al ., ). The mean maximum temperatures vary from 18·6°C in January to 39·1°C in May, and mean minimum temperatures vary from 5·2°C in December to 24·7°C in June.…”
Section: Methodsmentioning
confidence: 97%
“…Based on field experiments conducted in alluvial soils (Inceptisols), the reduction in maize and wheat yields was found to vary between 3.5% and 50.7% under different degrees of erosion (Khybri et al 1982). In the Shiwalik region of Punjab, a reduction of 103 kg ha -1 (91.9 lb ac -1 ) in maize grain yield was recorded with every centimeter (about 0.4 in) removal of topsoil (Sur et al 1998). Similarly, studies in black (Vertisols) soils indicated that loss of productivity of sorghum (Sorghum bicolor), pigeon pea (Cajanus cajan), groundnut (Arachis hypogaea), and soybean (Glycine max) crops was within 10%, 10% to 35%, and 35% to 50% under slight, moderate, and severe degrees of erosion, respectively (Yadav et al 1993).…”
mentioning
confidence: 99%